Yo-yo intermittent recovery test level 1 for young soccer player: Test-retest reliability - Kusuma, Ketut Chandra Adinata; Artanayasa, I Wayan; Yogi Parta Lesmana, Kadek (Jurnal Keolahragaan, 2025)
The data of intermittent endurance for soccer player is very needed by soccer coach to design the next training program. Therefore, a reliable instrument is needed to measure the endurance capacity. This study was aimed at examining the reliability of Yo-Yo Intermittent Recovery Test Level 1 (YYIRT Level 1) for amateur young soccer player aged 19 to 22 years. The players were devided into two groups, namely U-21 and U-23, and were instructed to complish three YYIRT Level 1 in three weeks. The comparison of mileage from the two groups was used to test the reliability of YYIRT Level 1 by using typical error (TE), coefficient of variation (CV), and intra-class correlation (ICC). The results showed that the average distance for YYIRT Level 1 performance in the U-21 and U-23 groups was 2404 ± 337 meters and 2475 ± 347 meters, respectively. Varying results were also reported for TE between 75 and 173 meters, CV between 3.0 and 6.9%, and ICC between 0.87 and 0.95 across age groups. Therefore, the performance of YYIRT Level 1 has proven to be very reliable in a sample of young soccer players, aged between 19 and 22 years. The intermittent endurance capacity shown in all age groups can be applied for measurements on other young players, both for determining prospective players and comparing performance between players.